Effects of carbon type and composition on the properties of carbon-copper composite as pantograph slide in railway application / Fazira Suriani Mohamed Fadzil ... [et al.] - Mohamed Fadzil, Fazira Suriani; Koay, Mei Hyie; Selamat, Mohd Asri; Abu Othman, Eliasidi; Mahaidin, Ahmad Aswad (UiTM Press, 2024)
Carbon-copper composites have wide application prospects as high-speed railway pantograph slides due to the self-lubricating ability of carbon and good conductivity of copper. However, carbon-copper composites produced through powder metallurgy may still encounter challenges, such as poor wettability and lower conductivity. The experimental approach in this work involved the fabrication of carbon-copper composites using the warm compaction method, with different types and proportions of carbon materials, namely local carbon from palm kernel shells (PKS) and graphite. Characterisation and testing of hardness, density, resistivity, transverse rupture strength (TRS), and microstructure of the composites have been conducted. An increase in graphite content was found to improve the electrical conductivity of the carbon-copper composite, while the addition of local carbon has enhanced its hardness. Furthermore, the addition of graphene oxide (GO) as filler has significantly improved the mechanical strength of this composite by up to 61.34%. This research has highlighted the potential of locally sourced carbon for developing advanced pantograph slide materials for railway applications. The findings provided valuable insights into the optimisation of composite compositions to achieve the desired balance between electrical conductivity and mechanical performance. These carbon-copper composites hold the promise of more efficient and durable pantograph slides, which can contribute to the overall reliability and sustainability of railway systems.